Flow-induced noise analysis for natural gas manifolds using LES and FW-H hybrid method. (February 2020) - Han, Tao; Wang, Lei; Cen, Kang; Song, Bin; Shen, Ruiqing; Liu, Hongbo; Wang, Qingsheng
Abstract: In this paper, the flow-induced noise generated by natural gas manifolds is analyzed . A noise experiment is carried out to validate the present numerical model. The characteristics of the flow-induced noise, including sound source distribution, sound directivity and frequency spectra, are investigated numerically. The effects of relevant parameters on overall sound pressure level are also analyzed quantitatively, including gas outlet pressure, inlet velocity, and the section area ratio of distribution pipe to inlet/outlet pipes. The main impact factors are evaluated using the orthogonal experimental design and the grey relational analysis method. Furthermore, proper noise reduction measures are also proposed. The results show that the manifold noise is middle and low frequency noise, and the energy of manifold noise is mainly concentrated in the range of 50–1150 Hz. The peak noise dominantly radiates at the directions of 75–105° along the gas flow. The gas inlet velocity should be controlled below 25 m/s. The optimal section area ratio of distribution pipe to outlet pipes should be below 2, while the section area ratio of distribution pipe to inlet pipes should be greater than 4. Gas inlet velocity and the section area ratio of distribution pipe to outlet pipes are the most important impact factors. In addition, some passive measures like noise absorption cover, and isolation hoods or walls, are recommended to reduce the flow-induced noise.